2012
DOI: 10.1007/s00276-011-0930-7
|View full text |Cite
|
Sign up to set email alerts
|

The demonstration of the number, course, and the location of nutrient artery canals of the femur by multidetector computed tomography

Abstract: In conclusion, the knowledge of the topographic features of the nutrient artery canals may be useful in various clinical implications such as bone grafting or radiologic evaluation for the fracture lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…Nutrient foramina transmit the nutrient artery through the diaphysis of the bone, supplying the medullary cavity with 70–80% of the nutrients and oxygen [ 12 , 13 ]. In long bones, these holes or foramina are found on the diaphysis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient foramina transmit the nutrient artery through the diaphysis of the bone, supplying the medullary cavity with 70–80% of the nutrients and oxygen [ 12 , 13 ]. In long bones, these holes or foramina are found on the diaphysis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we provided two regression models to estimate the relationship between height and TFD or length of nutrient artery canals, which are easier to calculate the location of foramina. In most previous studies, nutrient foramina were evaluated by their outer orifices macroscopically or direct radiography [ 11 13 , 15 , 19 – 22 ]. Earlier researchers gained anatomical information through cadavers which could be inevitably frayed and thus the accuracy of data could be affected.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the range of the foraminal index was from 24.5% to 42.9% and the mean value was 31.8%. It should be mentioned that Prashanth et al [ 19 ], Imre et al [ 15 ], and Sendemir and Cimen [ 28 ] reported that the range of I was 28–54%, 11.0–67.2%, and 30–40%, respectively. In Prashanth et al's research [ 19 ], they concluded that the location of the foramina would change with aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies evaluating numbers, locations, and levels of femoral nutrient foramina (Santolini et al 2014; Imre et al 2012; Murlimanju et al 2011a, b, c) have focused primarily on the shaft or diaphysis of the femur; few have been based on the MDCT (Imre et al 2012). None of those studies provided conclusive evidence concerning the number of foramina (Santolini et al 2014).…”
Section: Discussionmentioning
confidence: 99%